2005
DOI: 10.1055/s-2005-868519
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free Microwave-Assisted Synthesis of α-Aminophosphonates in a Three-Component System: R1C(O)R2-(EtO)2P(O)H-RNH2

Abstract: An effective catalyst-free microwave-assisted synthesis of a-aminophosphonates from ketones in a three-component system was shown. The method affords a-aminophosphonates in high yields from various ketones including natural porphyrine derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…In this way, instead of coordinating the tin(II) halide cocatalyst and leading to catalysts of low activities, the nitrogen atom will be protonated by the HCl liberated to form the platinum-hydrido species (8), the 'starting' complex of the catalytic cycle. According to a generally accepted mechanism of platinum-catalyzed hydroformylation, the coordination of the substrate provides the five-coordinated alkene complex (9). The insertion of alkene into the PteH bond results in the formation of the alkyl complex (10).…”
Section: Intermolecular Relations Of Molecular Structure 6b and The Smentioning
confidence: 99%
“…In this way, instead of coordinating the tin(II) halide cocatalyst and leading to catalysts of low activities, the nitrogen atom will be protonated by the HCl liberated to form the platinum-hydrido species (8), the 'starting' complex of the catalytic cycle. According to a generally accepted mechanism of platinum-catalyzed hydroformylation, the coordination of the substrate provides the five-coordinated alkene complex (9). The insertion of alkene into the PteH bond results in the formation of the alkyl complex (10).…”
Section: Intermolecular Relations Of Molecular Structure 6b and The Smentioning
confidence: 99%
“…Prolonged treatment of pure 9 with diethyl phosphite and indium chloride in tetrahydrofuran did not furnish 10b. Kabachnik et al showed that microwave acti-vation in the case of hindered ketones gave better results than conventional heating, [33] but in our case it was not helpful. Finally, a Pudovik-type reaction was investigated by using 9 as the starting material.…”
Section: Synthesis Of the α-Phosphonic Analogue Of Aminocitratementioning
confidence: 87%
“…Typically, a-aminoalkanephosphonates are formed in good yield by treating a carbonyl compound and an amine with a dialkyl phosphite in the presence of an organic base, an alkali metal alkoxide, or a Brønsted/Lewis acid. Recent preparative modifications of the reaction which significantly simplify the original method and increase the yield of the product concern the use of microwave irradiation [44][45][46][47][48][49], silica gel-supported reagents [43,46,49,50], surface-mediated reactions on Al 2 O 3 [51,52], ionic liquids as solvents [53], solvent-free conditions [43,44,47,54,55], and water-tolerant catalysts (magnesium perchlorate [56,57], lithium perchlorate [58,59], metal triflates [60][61][62], indium trichloride [63], samarium diiodide [64], lanthanide trichloride [65], TaCl 5 /SiO 2 [66], bismuth nitrate pentahydrate [67], scandium tris (dodecyl sulfate) [68], tetrabromomethane [54], and montmorillonite KSF [69]). …”
Section: Amidoalkylation In the Carbonyl Compound-amine-phosphite Thrmentioning
confidence: 99%